Jamaica : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Jamaica has achieved considerable success in reducing inflation, restructuring the financial system after the crisis in 1995-96, and further liberalizing the economy through tariff reduction and privatization. The government is urged to strengthen its efforts to put the economy on a less vulnerable path by a stronger fiscal adjustment supported by wage restraint, a more market-determined exchange rate, and an acceleration of structural reforms. The significant progress in structural reform made over recent years as well as the government's determination to continue is commendable.